Transition to a Low-Emissions Economy in Poland - Jorgensen, Erika (World Bank, Washington, DC, 2012)
Poland is not among the largest emitters of greenhouse gases globally, but its economy is among the least emissions-efficient in the European Union (EU). Poland's global share in greenhouse gas (GHG) emissions is just 1percent and its per capita emissions are similar to the EU overall. Its lower income level, the Polish economy comes out as among the least carbon-efficient. Poland's transition to a market economy since 1989 had a co-benefit of sharply reduced CO2 emissions; however, the link between growth and emissions has re-emerged in recent years. A critical difference in the make-up of Poland's emissions is the dominance of the power sector and its extraordinary dependence on coal. Over 90 percent of electricity in Poland is generated from coal and lignite, the highest share in the EU. This makes Poland an outlier, both globally and in Europe.